Antecedents of sustainable food waste management behaviour:empirical evidence from urban households in Malaysia - Nik Masdek, Nik Rozana (Walter de Gruyter GmbH, 2023)
Under the sustainability domain, food waste is a significant global challenge receiving growing attention. The management of household food waste which relies heavily on landfilling, is predominantly ineffective and unsustainable. To implement sustainable food waste management, an understanding of the individual behaviour is needed since psychological effects often undermine technological solutions. This study direct its investigation on urban households’ sustainable food waste management behaviour by extending the Theory of Planned Behaviour. An online survey was utilized for data collection. Using Partial Least Squares Structural Equation Modelling, assessments were made on the determinants of intention and behaviour of 520 households in the Klang Valley. The analysis support two factors that influence attitude positively, while five factors positively influence intention to implement best practices of reusing leftovers, separating household waste, and doing home composting. However, although the households have positive intentions, yet their composting practices seem to be the least adopted compared to the other sustainable elements. Addressing the lack of participation requires a holistic approach via dissemination of educational materials, social media coverage, and awareness campaigns. It is also suggested that composting be incentivized and be included in reward schemes similar to recycling. This study paves the way to enhance understanding of the factors to adopt sustainable food waste management among households in the urban areas. The findings provide insights for policy makers and other stakeholders on what type of information to consider when designing effective food waste management campaigns and urban development strategies, supporting the opportunity for consumer behavioural change.